Study On Serum Calcium and Magnesium in Preeclampsia - Dr. Arava Vineetha; Dr. Arava Vineetha; Dr. Jaya Nelli; Dr. Rajit Pokkula; Dr. B Ganesh (International Journal of Pharma and Bio Sciences, 2024)
Pre-eclampsia is one of the leading causes of maternal and fetal morbidity and mortality. It affects around 5-7 % of all pregnancies. The highest impact of pre-eclampsia was seen in developing countries, constituting 20-80% of maternal mortality. Enhancing calcium and magnesium intake can decrease pregnancy-induced hypertensive disorders. Prompt management helps in decreasing the incidence of complications. The study aims to assess serum calcium and magnesium levels among pre-eclampsia pregnant women. Objectives are to compare age, gestational age, BMI, BP, serum calcium, and magnesium levels among cases and controls and to check for the cutoff point of serum calcium and magnesium at which they can detect the presence of preeclampsia. Serum calcium and magnesium were assessed using a colorimetric method in the auto analyzer. All parameters were compared between cases and controls. There is a significant difference in the mean systolic, diastolic blood pressure, and body mass index between cases and controls. There is a significant difference in the mean serum calcium and magnesium levels between cases and controls. The area under the curve was 0.87 for magnesium levels in detecting preeclampsia. The area under the curve was 0.72 for calcium levels in detecting preeclampsia. Low calcium and magnesium levels could act as risk factors for preeclampsia. Hence, we recommend supplementing calcium and magnesium as a preventive measure against preeclampsia. There is no significant difference between the mean and gestational age between cases and controls.